Miliaria pustulosa misdiagnosed as a case of acne vulgaris - Iqbal Bukhari; Aala Alayoubi; Muhannad Alzahrani (Our Dermatology Online, 2016)
Miliaria is a skin disorder of eccrine glands. Based on the level of sweat duct obstruction, miliaria is subdivided into three main types: Miliaria crystallina, miliaria rubra and miliaria profunda. Besides, resident skin bacteria are thought to play a role in its pathogenesis. In this report we are presenting a case of miliaria pustulosa which was misdiagnosed initially as a case of acne vulgaris.